Pengaruh Prinsip Transparansi terhadap Kinerja Pegawai di Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Hulu Sungai Utara - Jumadi, Jumadi (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to determine the influence of the principle of transparency on employee performance at the Regional Development Planning, Research, and Development Agency (Bappedalitbang) of Hulu Sungai Utara Regency. The research employed a quantitative method with an associative approach. The study population consisted of all 32 employees of Bappedalitbang Hulu Sungai Utara Regency. Data were collected through questionnaires using a Likert scale. Data analysis was carried out using SPSS through validity tests, reliability tests, correlation analysis, and simple linear regression. The findings indicate that the principle of transparency has a very strong influence on employee performance, with a correlation coefficient (r) of 0.950 and a coefficient of determination (R²) of 0.902. This means that 90.2% of the variation in employee performance is influenced by the principle of transparency, while the remaining 9.8% is affected by other factors outside this study. A significance value of 0.000 (< 0.05) confirms that the hypothesis is accepted, indicating a positive and significant effect of transparency on employee performance.